(3OQGSGJ GdLOhi GdGbJUGOjI h Jbjje GdeTQhYGJ GdUfGYjIs - (3eOMJ cGXe(B, (3GdbQjTis ((3YeGf(B:s (3OGQ hGFd(B,s, 2009)
(3GdGWGQ GdYGe dOQGSGJ GdLOhi GdGbJUGOjI , CfhGY OQGSGJ GdLOhi GdGbJUGOjI , GdHjGfGJ h GdeYdheGJ GddGReI dOQGSI GdLOhi GdGbJUGOjI h Jbjje GdeTQhYGJ , eYGjjQ GdQHMjI GdJLGQjI GdNGUI dddeTQhYGJ , eYGjjQ GdQHMjI GdGbJUGOjI GdbhejI ddeTQhYGJ (B: (3GdWQb GdLRFjI h GdWQb GdTGedI , JMdjd GdQHMjI GdJLJdGjI h GdbhejI aj XQha GdeNGWQ h YOe GdJCcO , Jbjje GdGOGA aj GdefTBJ GdUfGYjI , MGdGJ JWHjbjI dJbjje GdeTQhYGJ GdUfGYjIs
(3eQGLY U(B.277((3GbJfGAGJ (B2014 3(3f(B)s
Keywords: (3GdeTGQjY GdUfGYjIs; (3Jbjje GdCOGAs